2015
DOI: 10.18805/ijar.5716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tanniferous leaf meal mixture based multi nutrient blocks on nutrient utilization and biochemical profile of Haemonchus contortus infected goats

Abstract: The experiment was carried out in 12 local adult male goats of average body weights (26.49±0.87, kg) and they were allocated in 3 groups (4 goats in each). Multi nutrient blocks (MNB) were supplemented in first two groups i.e. in T 1 (no infection) and T 2 (Haemonchus contortus infection @ 1500 larvae) group, while, condensed tannins (CT) containing multi nutrient blocks (MNB-CT) were supplemented in T 3 (H. contortus infection @ 1500 larvae) group in completely randomized block design during a feeding trial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Gastrointestinal parasitism in sheep and goats is directly associated with anemia and hypoproteinaemia resulting from endogenous protein and blood losses. Studies show that supplementation with CT containing forages alleviate impacts of parasitism in sheep and goats (Arroyo-Lopez et al, 2014;Singh et al, 2016). A pasture trial conducted by Merera et al (2013) showed that supplementation with Leucaene pallida significantly increased packed cell volume (PCV) of nematode infected Horro lambs compared to those assigned grazing alone.…”
Section: Effect Of Ct On Hematobiochemical Parameters Of the Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal parasitism in sheep and goats is directly associated with anemia and hypoproteinaemia resulting from endogenous protein and blood losses. Studies show that supplementation with CT containing forages alleviate impacts of parasitism in sheep and goats (Arroyo-Lopez et al, 2014;Singh et al, 2016). A pasture trial conducted by Merera et al (2013) showed that supplementation with Leucaene pallida significantly increased packed cell volume (PCV) of nematode infected Horro lambs compared to those assigned grazing alone.…”
Section: Effect Of Ct On Hematobiochemical Parameters Of the Hostmentioning
confidence: 99%
“…A number of studies have examined the effects of CT on different biochemical variables (hemoglobin, Protein, Implications of Tannin Containing Plants for Productivity and Health in Small Ruminant Animals: A Review urea, mast cells, pan cells, mean corpuscular cells, globulin, eosinophil) in parasitized sheep (Azuhnwi et al, 2013;Rios-De-Álvarez et al, 2014) and goats (Singh et al, 2016) receiving different tanniniferous forages. Azuhnwi et al (2013) reported increased in plasma essential and semiessential amino acids (AA) concentration in lambs artificially infected with H. contortus fed sainfoin.…”
Section: Effect Of Ct On Hematobiochemical Parameters Of the Hostmentioning
confidence: 99%
“…There are about 14.8 million goats in Bangladesh (DLS, 2015). Goat farming is crucially important for provision of milk, meat, hides and manures for human need that plays a great role in removing out of poverty and as a means of livelihood in the rural landless farmers in developing countries (Peacock et al, 2005;Hassan et al, 2007;Singh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%